2012
DOI: 10.1136/bmj.e5909
|View full text |Cite
|
Sign up to set email alerts
|

Indoor tanning and non-melanoma skin cancer: systematic review and meta-analysis

Abstract: Indoor tanning is associated with a significantly increased risk of both basal and squamous cell skin cancer. The risk is higher with use in early life (<25 years). This modifiable risk factor may account for hundreds of thousands of cases of non-melanoma skin cancer each year in the United States alone and many more worldwide. These findings contribute to the growing body of evidence on the harms of indoor tanning and support public health campaigns and regulation to reduce exposure to this carcinogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
258
2
9

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(275 citation statements)
references
References 47 publications
6
258
2
9
Order By: Relevance
“…However it should be noted that the body areas not being exposed to the sun earlier, also receive UV radiation with the current popularity of indoor tanning and sunbathing. [23,36] This is evident from the study of Hollestein et al [35] that SCC can also occur in the trunk and have an absolute risk of 2 per 100,000. But this is still low as compared to 11.9 per 100,000 for face.…”
Section: Absolute Risk From Nlo Biopsiesmentioning
confidence: 99%
“…However it should be noted that the body areas not being exposed to the sun earlier, also receive UV radiation with the current popularity of indoor tanning and sunbathing. [23,36] This is evident from the study of Hollestein et al [35] that SCC can also occur in the trunk and have an absolute risk of 2 per 100,000. But this is still low as compared to 11.9 per 100,000 for face.…”
Section: Absolute Risk From Nlo Biopsiesmentioning
confidence: 99%
“…14,15 Two recent studies provide estimates of the number of skin cancers that may be caused by indoor tanning each year; more than 170,000 cases of squamous and basal cell carcinomas of the skin may be due to indoor tanning in the U.S. annually, and more than 3400 cases of melanoma may be due to indoor tanning in Europe. 16,17 Melanoma causes more deaths than any other skin cancer, and its incidence is increasing, particularly among non-Hispanic whites and women; increases have also been noted among all tumor thicknesses. 18 Additionally, melanoma is one of the most commonly diagnosed cancers among adolescents and young adults in the U.S. 19,20 Indoor tanning before age 35 years increases the risk of melanoma by 60%-80% or more, possibly because of longer duration of use.…”
Section: Indoor Tanning and Cancer Riskmentioning
confidence: 99%
“…Two studies other than our earlier study investigated BCC occurrence in relation to age when exposed to indoor tanning. 22 The Nurse' s Health Study studied 73 494 female married nurses, of whom 5506 developed a BCC. In this study, number of times per year participants reported using a tanning bed was associated with risk of BCC, particularly among those who used tanning beds at a younger age, such as during high school or college; the relative risk for 4 times per year compared with no use in high school or college was 1.40, and for 25 to 35 years of age it was 1.19.…”
Section: Discussionmentioning
confidence: 99%